Pregunta
upstudy study bank question image url

Simplify: \( \frac{x^{4}+x}{x^{3}-x^{2}+x} \) Hence: 2.2.1 Determine the value of \( \frac{x^{4}+x}{x^{3}-x^{2}+x} \), if \( x=-3 \) 2.2.2 solve for \( x \) if: \[ \frac{x^{4}+x}{x^{3}-x^{2}+x}=2 \]

Ask by Klein Newton. in South Africa
Feb 25,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The simplified form of \( \frac{x^{4}+x}{x^{3}-x^{2}+x} \) is \( x+1 \). When \( x = -3 \), the expression equals \( -2 \). When \( \frac{x^{4}+x}{x^{3}-x^{2}+x} = 2 \), \( x = 1 \).

Solución

Calculate or simplify the expression \( (x^4+x)/(x^3-x^2+x) \). Simplify the expression by following steps: - step0: Solution: \(\frac{\left(x^{4}+x\right)}{\left(x^{3}-x^{2}+x\right)}\) - step1: Remove the parentheses: \(\frac{x^{4}+x}{x^{3}-x^{2}+x}\) - step2: Factor the expression: \(\frac{\left(x^{3}-x^{2}+x\right)\left(x+1\right)}{x^{3}-x^{2}+x}\) - step3: Reduce the fraction: \(x+1\) The simplified form of the expression \( \frac{x^{4}+x}{x^{3}-x^{2}+x} \) is \( x+1 \). Now, let's determine the value of \( \frac{x^{4}+x}{x^{3}-x^{2}+x} \) when \( x = -3 \). Substitute \( x = -3 \) into the expression \( x+1 \): \[ \frac{(-3)^{4}+(-3)}{(-3)^{3}-(-3)^{2}+(-3)} = \frac{81-3}{-27-9-3} = \frac{78}{-39} = -2 \] Therefore, when \( x = -3 \), the value of the expression is \( -2 \). Next, let's solve for \( x \) when \( \frac{x^{4}+x}{x^{3}-x^{2}+x} = 2 \). Set the expression equal to 2: \[ x+1 = 2 \] Solving for \( x \): \[ x = 2 - 1 = 1 \] Therefore, when \( \frac{x^{4}+x}{x^{3}-x^{2}+x} = 2 \), the value of \( x \) is 1.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Extra Insights

To simplify the expression \( \frac{x^{4}+x}{x^{3}-x^{2}+x} \), we start by factoring both the numerator and the denominator. In the numerator: \[ x^{4} + x = x(x^{3} + 1) = x(x + 1)(x^{2}-x+1) \] In the denominator: \[ x^{3} - x^{2} + x = x(x^{2} - x + 1) \] Now we can rewrite the expression: \[ \frac{x(x + 1)(x^{2}-x+1)}{x(x^{2}-x+1)} \] Assuming \( x \neq 0 \) and \( x^{2}-x+1 \neq 0 \), we can cancel \( x \) and \( (x^{2}-x+1) \): \[ \frac{x + 1}{1} = x + 1 \] Now, let's solve the subproblems: ### 2.2.1 To determine the value of \( \frac{x^{4}+x}{x^{3}-x^{2}+x} \) at \( x = -3 \): Substituting \( x = -3 \) into the simplified expression \( x + 1 \): \[ -3 + 1 = -2 \] So, \( \frac{x^{4}+x}{x^{3}-x^{2}+x} = -2 \) when \( x = -3 \). ### 2.2.2 To solve for \( x \) in the equation \( \frac{x^{4}+x}{x^{3}-x^{2}+x}=2 \): Using the simplified version \( x + 1 = 2 \): \[ x + 1 = 2 \] Subtracting 1 from both sides gives: \[ x = 1 \] Thus, the solutions are: \( \frac{x^{4}+x}{x^{3}-x^{2}+x} = -2 \) at \( x = -3 \), and \( x = 1 \) satisfies the equation \( \frac{x^{4}+x}{x^{3}-x^{2}+x} = 2 \).

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad